Exploiting maxillary sinus dimensions for sexual determination in the Bosnian and Herzegovinian population - Đukić Igor; Jezdić Zoran; Kadić Mirsad; Pirović-Kadić Anesa; Janković Ognjenka; Radulović Aleksandra; Arsić Ivan; Jakovljević Aleksandar; Nedeljković Nenad (Srpski Arhiv za Celokupno Lekarstvo)
Introduction/Objective. This study aimed to evaluate sex assessment using cone-beam computed tomography (CBCT) images by analyzing the dimensions and volume of the maxillary sinus. Additionally, the study aimed to develop prediction formulas for sex assessment and assess their accuracy for the population of Bosnia and Herzegovina. Methods. A total of 150 CBCT images were analyzed, comprising 73 males and 77 females, aged 20– 69 years. The dimensions of the maxillary sinuses – specifically, the mediolateral, superoinferior, and anteroposterior measurements – along with their volumes, were assessed using Romexis software. Measurements were taken from both axial and coronal projections. To develop gender prediction formulas, multiple regression analysis was employed. The accuracy of sex prediction was evaluated using discriminant functional analysis. Results. Significant differences (p < 0.05) in sinus dimensions and volume were observed between sexes. Males had larger maxillary sinuses: left sinus volume was 27.60 ± 6.87 cm3 in males versus 22.10 ± 5.77 cm3 in females and right sinus volume was 27.48 ± 7.02 cm3 in males versus 21.65 ± 5.42 cm3 in females. The right maxillary sinus provided the highest accuracy for sex prediction (75%), followed by the left sinus (71%). Conclusion. The dimensions and volume of the maxillary sinus vary significantly between sexes, with males typically having larger sinuses. A gender prediction formula based on the right maxillary sinus offers the highest accuracy for sex prediction, achieving 75%. This formula could be a valuable tool in forensic applications specific to the Bosnian population when other methods are not available.